2014
DOI: 10.1186/gb-2014-15-1-r12
|View full text |Cite
|
Sign up to set email alerts
|

Global target mRNA specification and regulation by the RNA-binding protein ZFP36

Abstract: BackgroundZFP36, also known as tristetraprolin or TTP, and ELAVL1, also known as HuR, are two disease-relevant RNA-binding proteins (RBPs) that both interact with AU-rich sequences but have antagonistic roles. While ELAVL1 binding has been profiled in several studies, the precise in vivo binding specificity of ZFP36 has not been investigated on a global scale. We determined ZFP36 binding preferences using cross-linking and immunoprecipitation in human embryonic kidney cells, and examined the combinatorial regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
170
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 146 publications
(178 citation statements)
references
References 60 publications
8
170
0
Order By: Relevance
“…mRNA stability can also be augmented by ARE interacting factors. The best-characterized example is the HuR protein, which competes with destabilizing factor for the binding to AREs and leads to the stabilization of the mRNA presumably by displacement of these factors (Lebedeva et al 2011;Mukherjee et al 2014). Likewise, binding of LARP4B to AU-rich sequences in the context of AREs might displace destabilizing factors similarly to the mechanism described for HuR.…”
Section: Discussionmentioning
confidence: 99%
“…mRNA stability can also be augmented by ARE interacting factors. The best-characterized example is the HuR protein, which competes with destabilizing factor for the binding to AREs and leads to the stabilization of the mRNA presumably by displacement of these factors (Lebedeva et al 2011;Mukherjee et al 2014). Likewise, binding of LARP4B to AU-rich sequences in the context of AREs might displace destabilizing factors similarly to the mechanism described for HuR.…”
Section: Discussionmentioning
confidence: 99%
“…Strikingly, the mRNA regulatory protein tristetraprolin (TTP; also known as ZFP36) was the most specifically upregulated RBP in the hippocampus by more than 200-fold. ZFP36 is known to destabilize mRNAs that encode cytokines and other inflammatory immune genes by recruiting the CCR4-NOT1 complex to AU-rich elements in the 3′ untranslated regions (3ʹUTRs) of targets, leading to deadenylation and subsequent degradation of mRNAs [178][179][180] . Recently, it was found that cytokines and other immune-regulatory proteins are expressed in the developing and adult nervous system, in which they are required for normal brain development and synaptic plasticity 181,182 .…”
Section: ʹ Untranslated Regionsmentioning
confidence: 99%
“…AU-rich elements (AREs) can be bound by several proteins such as Tristetraprolin (TTP) and the Hu protein family. There are thousands of overlapping TTP and HuR sites on the eukaryotic transcriptome, and depending which protein has the major effect, the mRNA is degraded (TTP) or stabilised (HuR) [20]. Of note, two members of the family, HuD [21] and HuR [22], play an important role in brain development and plasticity.…”
Section: Combinatorial Rna Recognition In the Cytoplasmmentioning
confidence: 99%